Maçã 'Royal Gala' revestida com quitosana estocada à temperatura ambiente - Jorge, Paula Canonico Silva [UNESP]; Nucci, Mariana [UNESP]; Janzantti, Natália Soares [UNESP]; Rizzo, Jackeline Salmeirão de; Assis, Odílio Benedito Garrido de; Monteiro, Magali [UNESP] (My University, 2011)
The aim of this work was to evaluate apples covered with chitosan during storage at ambient temperature. 'Royal Gala' apples were covered with chitosan (MRQ), immersed in acetic acid solution (MB) or did not receive any treatment (MC) and subsequently analyzed physicochemical, sensorial andinstrumentally, as well as for rotten occurrence, at zero, 7, 14, 21, 28, 35, 42 and 46 days of storage. The ratio, pH and reducing sugar contents increased while total titratable acidity, total sugars, total solids and firmness were reduced during storage. Was observed a drastically reduction of ascorbic acid and slight increase on soluble solids, except in the apples that were not pretreated (MC). Luminosity and chromaticity ratio values improved with time, with higher intensity in MRQ. Rotten occurrence was not expressive. The acceptance of appearance, color, global impression, aroma and flavor decreased with time, and appearance and texture were considered the most important sensory attributes for apples. The use of chitosan delayed ripening, reduced losses in firmness and presented a more intense bright, extending shelf life period up to seven days.
Royal Gala' apple covered with chitosan and stored at room temperature
Keywords: Chitosan coating; Malus domestica; Physicochemical characteristics; Post harvest; Sensory acceptance; Malus x domestica